The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/ccd.28841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insulin treated and non‐insulin‐treated diabetes compared to patients without diabetes on 1‐year outcomes following contemporary PCI

Abstract: Objective: We compared 1-year outcomes in insulin-treated diabetes mellitus (ITDM) and non-ITDM patients compared to nondiabetic (DM) patients following contemporary percutaneous coronary intervention (PCI). Background: ITDM is associated with extensive atherosclerotic disease and worse cardiovascular prognosis compared to non-ITDM patients. Methods: We evaluated PCI patients at a large tertiary center from 2010 to 2016, grouped according to diabetes and treatment status at baseline. One-year major adverse car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
8
1
Order By: Relevance
“…Since a smaller balloon size and lower inflation pressure would result in less injury to the vessel wall, the difficulty of achieving complete apposition to the vessel wall and inadequate strut embedment, the post-dilatation balloon size and post-dilatation balloon inflation pressure were negatively associated with uncoverage in this study. Although a previous article revealed that the negative prognostic effect of DM following contemporary PCI was heightened in the presence of insulin treatment [34], insulin therapy did not impact on the early-phase arterial healing in the current study. Instead, we observed that the use of sulfonylurea was an independent predictor of the minimum NIC of grade 0 in the DM patients.…”
Section: Discussioncontrasting
confidence: 80%
“…Since a smaller balloon size and lower inflation pressure would result in less injury to the vessel wall, the difficulty of achieving complete apposition to the vessel wall and inadequate strut embedment, the post-dilatation balloon size and post-dilatation balloon inflation pressure were negatively associated with uncoverage in this study. Although a previous article revealed that the negative prognostic effect of DM following contemporary PCI was heightened in the presence of insulin treatment [34], insulin therapy did not impact on the early-phase arterial healing in the current study. Instead, we observed that the use of sulfonylurea was an independent predictor of the minimum NIC of grade 0 in the DM patients.…”
Section: Discussioncontrasting
confidence: 80%
“…Percutaneous coronary intervention (PCI) has been generally recognized as a standard therapy to treat anatomical stenosis of coronary arteries. Nevertheless, current studies hold mixed opinions on the influence of diabetes on the prognosis of PCI 4 , 5 , 6 , 7 , 8 , 9 . Therefore, the impact of diabetes on the prognosis of patients who have undergone PCI is in need of reassessment brought by new approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, current studies hold mixed opinions on the influence of diabetes on the prognosis of PCI [4][5][6][7][8][9] . Therefore, the impact of diabetes on the prognosis of patients who have undergone PCI is in need of reassessment brought by new approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This disadvantage was evident both in patients undergoing revascularisation procedures and those who were conservatively treated. A recent analysis of PCI patients from New York confirmed these findings in more actual data: At one year, diabetes was associated with a 2.1× elevation in adverse event rates (MACE) in insulin-treated DM (ITDM) and with a HR of 1.27 in non-ITDM after PCI [20]. In the GRACE multinational registry, diabetes proved to be an independent factor to predict in-hospital and 6-month mortality in patients with ACS.…”
Section: Impact Of Diabetes On Adverse Ischemic Events and Mortality In Patients With Cad And Cad-eventsmentioning
confidence: 78%